Social structure and integration: Occupational classes and integration mechanisms between 2015 and 2021 - Kovách, Imre; Kristóf, Luca (Intersections. East European Journal of Society and Politics, 2024)
The topic of the paper is the relationship between social stratification based on occupational classes and the mechanisms of social integration, which was analysed on quantitative data collected in 2015, 2018 and 2021. We sought answers to how we can better understand the interaction of social and integration positions, as well as the functioning of complex integration mechanisms. In the examined six years, a definite homogenization took place in the integration indicators of the occupational groups: this means that indicators measured of occupational group in some integration dimensions took on closer values. It is also part of our research results that there is an interpretable correlation between the hierarchy of occupational groups and the examined integration mechanisms: political participation, number of weak ties, subjective social exclusion and acceptance of norm violation. The upper strata of the occupational class model (mostly entrepreneurs, managers, professionals and other white-collar workers) have consistently reported higher numbers of weak ties, lower sense of exclusion and higher political participation. We also found consistent, yet opposite results in the lower strata, mostly among the unemployed and those with unskilled and semi-skilled work linked to lower qualifications. The strengthening of homogenization and the impact of the hierarchy of occupational groups are simultaneous integrational characteristics of Hungarian society. The future research question is whether homogenization rearranges the integration effect of the occupational hierarchy.